“Soulful” – - a symbol of loyalty to the motherland and the nation (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
Maqsud Shaikhzoda through this work glorified the spiritual power, courage and longing for freedom of the Uzbek people. "Soulful" is a poetic collection in which the poet reacts to the complex socio-political events of his time. The poems in it reflect the high feelings of the human soul, love and courage for the motherland.